Emotional labor and burnout among female teachers: work-family conflict as mediator - Noor, Noraini M.; Zainuddin, Masyitah (Blackwell Publishing Asia Pty Ltd, 2011)
With the increasing number of women in the workforce, there is a need to understand how the interrelationship between emotions and the demands of work and family influence their well-being. This study examined how emotional labor [surface acting (SA) and deep acting] and work–family conflict contribute to explaining variance in burnout (emotional exhaustion and depersonalization). In a sample of 102 married, female Malay teachers, with at least one child living at home, results showed that SAwas positively associated with emotional exhaustion and depersonalization. The results also showed that work–family conflict mediated the relationship between emotional labor and burnout. However, no moderation effect of work–family on the SA–burnout relationship was found. The results are discussed with respect to the general literature on the stress–strain relation and work– family conflict.